2016
DOI: 10.5935/1678-9741.20160080
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Risk After Cardiac Surgery: Application of Inscor in a University Hospital in Brazil's Northeast

Abstract: ObjectiveTo apply the InsCor in patients undergoing cardiac surgery in a university hospital in Brazil's northeast.MethodsIt is a retrospective, quantitative and analytical study, carried out at the University Hospital of the Federal University of Maranhão. InsCor is a remodeling of two risk score models. It evaluates the prediction of mortality through variables such as gender, age, type of surgery or reoperation, exams, and preoperative events. Data from January to December 2015 were collected, using a Physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 12 publications
0
14
0
6
Order By: Relevance
“…In our country, Silva et al [16] showed an operative mortality rate of 4.0% in patients operated by the Unified Health System (SUS) at the Hospital Beneficência Portuguesa in São Paulo, while Fortes et al [16,17] showed an average mortality of 7.4% in patients referred for CABG in a university hospital in northeastern Brazil. TotalCor Hospital, a private hospital focused on cardiology, points to a mortality rate of 1.7%.…”
Section: Discussionmentioning
confidence: 99%
“…In our country, Silva et al [16] showed an operative mortality rate of 4.0% in patients operated by the Unified Health System (SUS) at the Hospital Beneficência Portuguesa in São Paulo, while Fortes et al [16,17] showed an average mortality of 7.4% in patients referred for CABG in a university hospital in northeastern Brazil. TotalCor Hospital, a private hospital focused on cardiology, points to a mortality rate of 1.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Acute renal injury (AKI) is a severe complication that occurs in 3.5-31.0% of patients undergoing cardiac surgery, making it one of the most common complications observed in this group of patients [ 1 ] . In a study conducted by Kochi et al [ 2 ] , the prevalence of postoperative AKI among cardiac surgery patients was 34.0%.…”
Section: Introductionmentioning
confidence: 99%
“…With the technique of cardiac surgery booming in the big developing countries like China, Brazil and India, more and more complex procedures can be performed. Meanwhile, the following complications of surgery may emerge as well, which will be a huge burden of national health cost [ 1 ] . Acute kidney injury (AKI) is one of these common complications after cardiac surgery with reported incidences over 30% while mortality increased fourfold and even slight renal function changes were reported to influence short- and long-term survival rates after cardiac surgery [ 2 , 3 ] .…”
Section: Introductionmentioning
confidence: 99%